Realization of Theme on Malaysia Tourism e-Brochure - Eka Sari; Rodey Hamzah; Dian Asa Utari; Miftachudin (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
E-brochure as one kind of promotion media reaches vast audience in short time to promote Malaysian tourism spots. Analyzing the occurrence of theme on e-brochure is expected to help Malaysian tourism providers create interesting and efficient promotion media. Theme works as the glue that structures meanings in a clause. This research aims to analyze themes on Malaysia tourism e-brochure in forms of topical, textual, and interpersonal themes. The analysis is done using thematic development proposed by Gerot and Wignell (1994). This research is descriptive qualitative research. The objects are e-brochures of seven tourism spots in Malaysia. They are Langkawi, Penang, Pangkor, Port Dickson, Islands of Johor, Tioman, and Malaysia in general. They are chosen randomly to make the analysis objective. There are 183 clauses that work as the data. The analysis shows that most of the themes on Malaysia e-brochure are in forms of topical theme. The emergence of topical theme in the analysis are mostly in forms of noun and noun phrase. Analyzing types of themes is helpful to make the focus of the meaning on Malaysia e-brochure delivered well as it plays a crucial role in contributing the coherence on it.